If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(8 + 3k) = 116 (8 * 4 + 3k * 4) = 116 (32 + 12k) = 116 Solving 32 + 12k = 116 Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '-32' to each side of the equation. 32 + -32 + 12k = 116 + -32 Combine like terms: 32 + -32 = 0 0 + 12k = 116 + -32 12k = 116 + -32 Combine like terms: 116 + -32 = 84 12k = 84 Divide each side by '12'. k = 7 Simplifying k = 7
| x+(2x+4)=7 | | 5(x+2)=7(x) | | -4(3+4n)=-140 | | ln(4x^2-20x+24)= | | Solve(7x+2)2=64 | | 8*9=6x*12x | | (7-z)(5z-4)=0 | | -3+x-5((2x+4)-(x+2))=x+2 | | 14x^2-209x-15= | | 125=5(3v+7) | | b^2-4b-7=0 | | 10x-6=5x+10 | | e^4x=102.9 | | e(4x)=102.9 | | -4(1+8v)+3v=-178 | | 7(6-7x)=-105 | | 4x^2+5=x | | 4x^2-3x-9-(2x^2+22x+27)=0 | | 8(4x+8)-1=287 | | 2x^2-25x-36=0 | | 7(5-3n)=-112 | | x*3+10=11+x | | 7(1-5n)=182 | | 4=2e^14x-1 | | 85=n-6(-n-6) | | 6(x-2)+6=4(2x-6) | | 6x-1=11x-11 | | 6(1+3p)=-138 | | 2x-42=-6(x+3) | | (15+11x)=(18+8x) | | 2+5(8n+3)=217 | | 15+11x=y |